Similarity in symptom patterns of posttraumatic stress among disaster-survivors: a three-step latent profile analysis - Kristina Bondjers; Mimmie Willebrand; Filip K. Arnberg (European Journal of Psychotraumatology, 2018)
Background: Individuals express symptoms of posttraumatic stress in various ways, noted for example in the many symptom combinations in the diagnostic manuals. Studies aiming to examine differences of symptom presentations by extracting latent classes or profiles indicate both the presence of subtypes with differing symptomatology and subtypes distinguished by severity levels. Few studies have examined subtype associations with long-term outcomes. Objective: The current study aimed to apply latent profile analysis on posttraumatic stress (PTS) in a highly homogenous sample of Swedish tourists exposed to the 2004 Southeast Asia tsunami and to examine if classes differed in their long-term outcome. Methods: An latent profile analysis was conducted using self-report data collected one year after the disaster from 1638 highly exposed survivors that endorsed ≥ 1 symptom of PTS. Associations were examined between the classes and predictors of PTS (loss of a relative or friend, subjective life threat) and levels of PTS at a three-year follow up. Results: The latent profile analysis indicated four classes: minimal, low, moderate, and severe symptoms. The classes were distinguished mainly by their levels of PTS. Loss of a relative or friend and subjective life threat were associated with a higher likelihood of belonging to any other class than the minimal class. The severity level of the classes at one year were predictive of PTS severity at the three-year follow-up. Conclusions: Homogeneous profiles of posttraumatic stress differing mainly in symptom severity were found in this sample of disaster survivors. Profile diversity may be related to sample variation and unmeasured confounders rather than reflect qualitatively different disorders.